Ang mito ng aklasang Basi - Feleo, Roberto (Ilocos, Norte Province of Ilocos Norte, 2016)
Contains Roberto Feleo's collection of art works and illustrations in his exhibition entitled, "Ang mito ng aklasang Basi"
Clouds and comet over wine warriors --
Life and limb for spirit --
Ang mito ng aklasing basi --
Alingas --
Tambolero --
The enlightened --
Kapit sa palaso --
Salorogo ambaristo --
Ang bangkero --
The hangman --
Pedro Mateo --
Pentimiento --
Nuestra senora de bola --
Dragon --
Fr. Abella --
Ang Tiktik
Keywords: Feleo, Roberto Bulatao -- 1954— -- Exhibitions